Analisis Pengaruh Sektor Pertaian Terhadap PDRB Sektor Pertanian di Indonesia Tahun 2015-2021 - Marcelina Anggreani; Arivina Ratih; Muhammad Husaini; Zulfa Emalia; Moneyzar Usman; Neli Aida; Ukhti Ciptawaty (Journal on Education, 2023)
The agricultural sector in Indonesia is an important sector in the national economy, but its role in the formation of GRDP in most regions is starting to decline. This was followed by a decrease in the area of ​​harvested land. The purpose of this study is to see the agricultural sector which acts as the basis sector in each province in Indonesia, and to determine the effect of domestic investment in the agricultural sector, the area of ​​paddy fields, and the agricultural sector's workforce on the GRDP of the agricultural sector. The data in this study were obtained from BPS and the Investment Coordinating Board (BKPM). This study uses panel data analysis with the selected model Fixed Effect Models (FEM) with the Eviews 10 application. This study also uses the Location Quotient (LQ) method to see the role of the base sector. The results of this study indicate that the agricultural sector is the basis sector in the provinces of Aceh, North Sumatra, West Sumatra, Riau, Jambi, South Sumatra, Bengkulu, Lampung, Kep. Bangka Belitung, Central Java, Bali, West Nusa Tenggara, East Nusa Tenggara, West Kalimantan, Central Kalimantan, South Kalimantan, North Kalimantan, North Sulawesi, Central Sulawesi, South Sulawesi, Southeast Sulawesi, Gorontalo, West Sulawesi, Maluku and North Maluku. This study also found that the variable PMDN in the agricultural sector had a significant positive effect, the variable paddy field area had a significant negative effect and the agricultural sector labor variable had no significant effect on the GRDP of the agricultural sector in Indonesia.